2023
DOI: 10.1111/1440-1681.13759
|View full text |Cite
|
Sign up to set email alerts
|

Bach1 modulates AKT3 transcription to participate in hyperglycaemia‐mediated EndMT in vascular endothelial cells

Abstract: Hyperglycaemia‐mediated endothelial‐to‐mesenchymal transition (EndMT) is involved in the occurrence and progression of cardiovascular complications in diabetic patients. Previous studies reported that AKT serine/threonine kinase 3 (AKT3) and Bric‐a‐brac/Tramtrack/Broad (BTB) and cap'n'collar (CNC) homology 1 (bach1) participates in endothelial injury and epithelial‐to‐mesenchymal transition. In the present study, we proposed that bach1 regulates AKT3 transcription, thus involved in hyperglycaemia‐mediated EndM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This is in keeping with previous data showing BACH1 levels remain elevated during the first 48h post MI in the murine left ventricular myocardium 24 and microarray data from human circulating endothelial cells demonstrating elevated BACH1 expression after MI 25 . Furthermore, other cardiovascular risk factors such as elevated glucose 26 and aging 27 have also been associated with increased BACH1 expression in the mouse aorta and heart respectively. For aging, this was further linked to increased endothelial cell senescence when under oxidative stress 27 .…”
Section: Discussionmentioning
confidence: 99%
“…This is in keeping with previous data showing BACH1 levels remain elevated during the first 48h post MI in the murine left ventricular myocardium 24 and microarray data from human circulating endothelial cells demonstrating elevated BACH1 expression after MI 25 . Furthermore, other cardiovascular risk factors such as elevated glucose 26 and aging 27 have also been associated with increased BACH1 expression in the mouse aorta and heart respectively. For aging, this was further linked to increased endothelial cell senescence when under oxidative stress 27 .…”
Section: Discussionmentioning
confidence: 99%
“…EndMT models were therefore designed with EC from these different origins and treated with high glucose concentrations in order to mimic hyperglycemia. HUVEC is widely used as a model for diabetes-associated cardiac fibrosis [ 14 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. In particular, Yu et al showed that 24 h treatment with 30 mM glucose resulted in the expression of the mesenchymal markers α-SMA and type I collagen in HUVEC.…”
Section: Existing In Vitro Models Of Endothelial To Mesenchymal Trans...mentioning
confidence: 99%